Logan multi-functional digital clock / Nik Nur Aneesa Zamzurri ... [et al.] - Zamzurri, Nik Nur Aneesa; Ali, Norarifah; Abdul Karim, Izza Syahida (Universiti Teknologi MARA, Kedah, 2021)
The term “reverse engineering” refers to an activity that is a process step by step by which the details design of a product is analysed, study, observe or redesign using a physical part as a starting point. This paper presents results of a study about re-design an existing digital clock through reverse engineering process and giving a new meaning of usage and form without changing the internal component of the digital clock product. Nowadays, people relies on alarm clocks to start the day. Digital clocks are becoming too popular because their advantages make it easy for you to check the time quickly, accurately and correctly. Logan multi-functional a digital clock is a type of clock that displays the current time with a digital method in 12 hour format as HH:MM:SS. This product features a multifunction 6 in 1: clock, alarm clock, temperature, calendar, timer and the light of the clock will get on by clapping. To see the current time, just tap the snooze button and you'll get five seconds of time shown. A built-in night light allows easy viewing of the time in the dark with a gentle hit on the table within the range of 1 meter by touching any place on product, in convenience of reading the time at night. Then, the light will automatically go off in just 5 seconds. This product with Temperature Humidity Sensor can accurately detect the temperature and humidity in your house. This product features a large display with oversized red numbers against a black LED display. The time can be set 12 hours or 24 hours easily or see time from a distance hands free. This clock uses Triple A Batteries. This product is specially designed for teenagers to help them normalize their sleep schedule and help them focus on getting the shut-eye. Plus, this product ensures them wouldn't miss out on important meeting or classes, so they can snooze away peacefully. This product is designed with three colour combination from black, merlot and alloy orange. These options are for users to pick which one suits their room better. This product is made out of ABS Plastic which also known as Acrylonitrile Butadiene Styrene as it is widely used in electronic housings, auto parts, consumer products, pipe fittings, Lego toys and more. This multi-functional device is ideal for traveling due to its compact and handy size.